New England Regional Student Program, Graduate Level 1975-1976 - New England Board of Higher Education, Wellesley, MA.; New England Board of Higher Education, Wellesley, MA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The New England Regional Student Program provides major savings to both the participating student and the New England state government. Students qualifying for study under the program receive admissions preference among out-of-state applicants and are charged only the equivalent of the in-state tuition fees. These are the arrangements agreed to by each of the participating institutions. This catalogue provides a listing of graduate degree opportunities at state universities open to residents of Connecticut, Maine, Massachusetts, New Hampshire, Rhode Island, and Vermont. Graduate degree opportunities at state colleges are listed by master's degree curricula and certificates of advanced graduate study listings. For a listing at the undergraduate level, see HE 006 106. (MJM)
Availability: New England Board of Higher Education, 40 Grove Street, Wellesley, Massachusetts 02181 ($2.00).
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Admission (School); Doctoral Degrees; Educational Opportunities; Educational Programs; Graduate Students; Higher Education; Interstate Programs; Masters Degrees; Out of State Students; State Colleges; State Universities; Tuition; New England Regional Student Program; Connecticut -- Maine -- Massachusetts -- New Hampshire -- Rhode Island -- Vermont; Guides, General